2003
DOI: 10.1121/1.1612493
|View full text |Cite
|
Sign up to set email alerts
|

Improved temporal coding of sinusoids in electric stimulation of the auditory nerve using desynchronizing pulse trains

Abstract: Rubinstein et al. [Hearing Res. 127, 108-118 (1999)] suggested that the representation of electric stimulus waveforms in the temporal discharge patterns of auditory-nerve fiber (ANF) might be improved by introducing an ongoing, high-rate, desynchronizing pulse train (DPT). To test this hypothesis, activity of ANFs was studied in acutely deafened, anesthetized cats in response to 10-min-long, 5-kpps electric pulse trains that were sinusoidally modulated for 400 ms every second. Two classes of responses to sinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 48 publications
(109 reference statements)
6
81
0
Order By: Relevance
“…Certainly we would expect accurate place/pitch matching to yield better results, as has been shown in some studies (Long et al 2003;Wilson et al 2003). Other studies, however, have shown that ITD information can be obtained even over a range of as many as eight contacts, spanning many millimeters in the cochlea (van Hoesel and Clark 1997).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Certainly we would expect accurate place/pitch matching to yield better results, as has been shown in some studies (Long et al 2003;Wilson et al 2003). Other studies, however, have shown that ITD information can be obtained even over a range of as many as eight contacts, spanning many millimeters in the cochlea (van Hoesel and Clark 1997).…”
Section: Discussionmentioning
confidence: 68%
“…Implant listeners tend to have acute sensitivity to the presence of amplitude modulation (Shannon 1992), but there is some evidence that the ability to detect small changes in stimulus rate is relatively poor (Zeng 2002). Furthermore, in at least one case, better ITD discrimination was found for an electrode pair that was mismatched in place/pitch than for the matched pair (Long et al 2003). It is tempting to suggest that in this case, the matched pair was in the saturated range and the better result with the mismatched pair was caused by moving into a nonsaturated state, similar to off-CF listening.…”
Section: Effects Of Sound Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…Different approaches for artifact removal can be found in the literature, ranging from the use of linear and nonlinear filters (Whittington et al 2003(Whittington et al , 2005Sennels et al 1997;Parsa et al 1998;Gnadt et al 2003;Liang and Lin 2002) to the subtraction of artifact templates generated by a variety of methods (Hashimoto et al 2002;Lin et al 1996;Lin and McCallum 1998;Wagenaar and Potter 2002;Litvak et al 2003;Yuwaraj and Kunov 1995;Grieve et al 2000;Blogg and Reid 1990). For multielectrode recordings with a high number of recording electrodes, blind source separation, independent component analysis, and optimized differential reference techniques allow for the spatial localization of artifact sources and potentials (Gilley et al 2006; Castañeda-Villa and James , which makes it possible to select electrodes that are less affected by artifacts and to remove artifact components from these recordings.…”
Section: Artifact Reductionmentioning
confidence: 99%